Gasdermin D: A New Inflammatory Biomarker in Assessing Clinical Disease Activity in Crohn’s Disease - Buldukoglu, Osman Cagin; Ocal, Serkan; Atar, Galip Egemen; Kaya, Besir; Isik, Muhammet Devran; Aydin Tigli, Gul; Akca, Serdar; Akbay Harmandar, Ferda; Cekin, Yesim; Cekin, Ayhan Hilmi (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Crohn’s disease (CD) is an inflammatory, progressive disorder requiring monitoring of treatment response and disease course. Gasdermin D (GSDMD), a protein belonging to the gasdermin protein family, plays a role in inflammatory cell death, and activation of GSDMD has been shown to be a component of the pathogenesis of inflammatory bowel disease. Considering the role that GSDMD plays in inflammation, it was hypothesized that disease activity in CD may be correlated with serum GSDMD levels. The aim of this study was to assess the strength of GSDMD in predicting clinical disease activity in patients with CD in a prompt and easy manner. Materials and Methods: This cross-sectional study was conducted over a span of 22 months from September 2022 to June 2024. A total of 61 patients with CD were included in the study. Demographic data, disease- and treatment-related data, and laboratory workups of the patients were recorded and analyzed. Results: Gasdermin D levels were statistically significant in their correlation with the Harvey–Bradshaw Index (HBI) scores of the study population (P = .019). A threshold value of 5 ng/mL for GSDMD had a sensitivity of 84.6% and a specificity of 91.7% in differentiating patients with remission or mild disease from those with moderate or severe disease, according to HBI. Conclusion: This pioneering study revealed that serum GSDMD can be used as a biomarker to assess clinical disease activity in patients with CD. Future studies incorporating colonoscopic evaluation into the equation will provide more insight into the use of this protein as a surrogate marker of disease progression in CD. Cite this article as: Buldukoglu OC, Ocal S, Atar GE, et al. Gasdermin D: A new inflammatory biomarker in assessing clinical disease activity in Crohn’s disease. Turk J Gastroenterol. 2025;36(9):556-562.